2014
DOI: 10.1108/maj-11-2013-0964
|View full text |Cite
|
Sign up to set email alerts
|

(Un)useful risk disclosure: explanations from the Italian banks

Abstract: Purpose – The purpose of this paper is to better understand how mandatory risk categories are disclosed and to provide a better understanding of the reasons why risk disclosure looks less useful than it ought to be. Design/methodology/approach – We analyze how Italian banks provide risk information, by focusing on its characteristics to find out any differences between the notes to the financial statements and the public report, both pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 36 publications
5
50
0
Order By: Relevance
“…The second category, pertaining to specific areas, includes studies of business combination and goodwill impairment test disclosures in Europe (Glaum, Schmidt, Street, & Vogel, 2013;Mazzi et al, 2017), Australia (Bepari & Mollik, 2015;Bepari, Rahman, & Taher, 2014;Guthrie & Pang, 2013), Singapore (Carlin, Finch, & Khairi, 2010), the Netherlands and Sweden (Hartwig, 2015); studies of financial instrument disclosures in Italy (Maffei, Aria, Fiondella, Spanò, & Zagaria, 2014), Portugal (Lopes & Rodrigues, 2007), the UK (Linsley & Shrives, 2006;Woods & Marginson, 2004), the US (Lu & Mande, 2014) and in European banks (Bischof, 2009 ); studies of segment disclosures in global IAS-adopter samples, primarily European (Prather-Kinsey & Meek, 2004;Street & Nichols, 2002), 8 Germany (Franzen & Weißenberger, 2015), the US (Chen & Liao, 2015); studies of disclosure compliance in relation to financial statement presentation disclosures in the UK (Iatridis & Valahi, 2010); share-based payment and executive compensation disclosures in Australia (Bassett, Koh, & Tutticci, 2007), France (Goh, Joos, & Soonawalla, 2016) and the US (Robinson, Xue, & Yu, 2011); contingent liabilities in the US (Hennes, 2014) and intangible assets in Italy (Devalle, Rizzato, & Busso, 2016).…”
Section: Disclosure Compliance Levels -Empirical Results and Methodologymentioning
confidence: 99%
“…The second category, pertaining to specific areas, includes studies of business combination and goodwill impairment test disclosures in Europe (Glaum, Schmidt, Street, & Vogel, 2013;Mazzi et al, 2017), Australia (Bepari & Mollik, 2015;Bepari, Rahman, & Taher, 2014;Guthrie & Pang, 2013), Singapore (Carlin, Finch, & Khairi, 2010), the Netherlands and Sweden (Hartwig, 2015); studies of financial instrument disclosures in Italy (Maffei, Aria, Fiondella, Spanò, & Zagaria, 2014), Portugal (Lopes & Rodrigues, 2007), the UK (Linsley & Shrives, 2006;Woods & Marginson, 2004), the US (Lu & Mande, 2014) and in European banks (Bischof, 2009 ); studies of segment disclosures in global IAS-adopter samples, primarily European (Prather-Kinsey & Meek, 2004;Street & Nichols, 2002), 8 Germany (Franzen & Weißenberger, 2015), the US (Chen & Liao, 2015); studies of disclosure compliance in relation to financial statement presentation disclosures in the UK (Iatridis & Valahi, 2010); share-based payment and executive compensation disclosures in Australia (Bassett, Koh, & Tutticci, 2007), France (Goh, Joos, & Soonawalla, 2016) and the US (Robinson, Xue, & Yu, 2011); contingent liabilities in the US (Hennes, 2014) and intangible assets in Italy (Devalle, Rizzato, & Busso, 2016).…”
Section: Disclosure Compliance Levels -Empirical Results and Methodologymentioning
confidence: 99%
“…Content analysis has been widely used in accounting research to measure corporate risk disclosure in annual reports (Linsley and Shrives, 2006;Abraham and Cox, 2007;Greco, 2012;Hill and Short, 2009;Maffei et al, 2014;Elzahar and Hussainey, 2012;Al-Najjar and Abed, 2014;Li, 2010). As a well-established method, content analysis is applied "for making replicable and valid inferences from texts to the contexts of their use" where reproducibility of findings plays an essential role (Krippendorff, 2004, p.18).…”
Section: Dependent Variable: Risk Disclosurementioning
confidence: 99%
“…Prior research shows that the level of banks' risk disclosure has increased over time, following an increase in minimum requirements imposed (e.g., Bischof, 2009). However, risk reporting's usefulness for decisionmaking has not improved at a similar rate (Pérignon and Smith, 2010;Maffei et al, 2014). Recent studies have found risk reporting to be unclear, very general and qualitative, not sufficiently forward-oriented, noncomparable and, thus, unhelpful for the assessment of risk exposure on an on-going basis (e.g., , Woods et al, 2008aOliveira et al, 2011b;Maffei et al, 2014).…”
Section: Risk Reporting In the Banking Sectormentioning
confidence: 99%
“…Inaccurate design can mislead the annual report's readers, with or without an accounting experience (Muiño and Trombetta, 2009;Pennington and Tuttle, 2009). The quality of risk reporting could be affected by the level of risk the bank faces (e.g., Maffei et al, 2014). …”
Section: H1: Banks Are Less Likely To Portray Credit Risk Graphs Whenmentioning
confidence: 99%
See 1 more Smart Citation